Mitigasi Bencana Lahar Hujan Gunungapi Merapi Berbasis Sistem Informasi Geografis dan Penginderaan Jauh di Sub DAS Kali Putih Kabupaten Magelang - Shinta, Dewi; , Dr. Kuswaji Dwi Priyono, M.Si; , Agus Anggoro Sigit, S.Si., M.Sc (2015)
Merapi Volcano eruption disaster that occurred in 2010 and resulted in many victims both mental and material. The impact of the eruption of Merapi Volcano that still can be seen today include rain overflowing lava material with a large volume. The resulting material loss for the region in its path. The purpose of this study were (1) to determine the distribution of potential lava rain; and (2) analyzing the lava disaster mitigation rain. The method used in this research is by way of interpretation of Landsat TM in 2006 to obtain primary data landforms, while the other secondary data required is land use, slope, rainfall, and the distance of the river. These data then becomes the data parameters are then be overlaid toobtain a distribution map lava rain Vulnerability. Insecurity lava rain map became survey to determine the actual conditions in the field, can be used to determine the route evakusi towards Evakusi The End (TEA) which has been provided by the government of Magelang district if at any time a natural disaster strikes. The results obtained from this study in the form of insecurity distribution lava rain map and disaster mitigation. The conclusion that can be derived from this study are (1) the distribution of vulnerability lava raining contained in the districts Salam, District Ngeluwar and District Srumbung (2) identification of the route evacuation efficient and can be passed to get to the place Evacuation Final (TEA) or refuge safe.